Innate immune evasion by alphaviruses - Liu, Yihan; Yuan, Yupei; Zhang, Leiliang (Frontiers in Immunology, 2022)
Alphaviruses contain many human and animal pathogens, such as CHIKV, SINV, and VEEV. Accumulating evidence indicates that innate immunity plays an important role in response to alphaviruses infection. In parallel, alphaviruses have evolved many strategies to evade host antiviral innate immunity. In the current review, we focus on the underlying mechanisms employed by alphaviruses to evade cGAS-STING, IFN, transcriptional host shutoff, translational host shutoff, and RNAi. Dissecting the detailed antiviral immune evasion mechanisms by alphaviruses will enhance our understanding of the pathogenesis of alphaviruses and may provide more effective strategies to control alphaviruses infection.